Production of Vanillin from Pineapple Peels Using Alkaline Hydrolysis and Microbial Fermentation - Zainurin Zubaidah; Latiffah Karim (USIM PRESS, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 10 Issue 1 Page (58-68)